Mail vs. telephone surveys of criminal justice attitudes: A comparative analysis - Farnworth, Margaret (Journal of quantitative criminology, 1996)
This study compares results from surveys using two modes of administration. A subset of questions from the 1992 Texas Crime Poll , a statewide poll conducted annually by mail, was replicated in telephone interviews using the Computer Assisted Telephone Interviewing System. The phone survey yielded better participation rates but less complete responses to individual attitude questions than did the mail poll. As expected, the mail survey was less expensive but less efficient than the automated phone survey. The central finding was that all but one of the responses to five attitude questions difered significantly across the surveys. The samples differed in their demographic composition, but this did not explain differences in the substantive findings from the mail and phone surveys. The discussion considers alternative explanations for differences in the findings from the two surveys and suggests direction for further comparative research.